PTH-277 Thirteen year review of how 2-week wait referrals and heightened awareness of colorectal cancer has affected stage at presentation. (22nd June 2015) - Fairhurst, K; Silavant, M; Bunni, J; Cook, T; Scott, M
Abstract : Introduction: Colorectal cancer is the third most commonly diagnosed cancer in the UK, and second most common cause of death related to cancer. It is widely acknowledged that the stage of colorectal cancer at presentation has prognostic significance and that earlier stage correlates with improved survival. The introduction of the 2-week wait system for referral of suspected cases of colorectal cancer and campaigns to increase awareness in both primary care and the general public, aim to facilitate earlier diagnosis and treatment. We assessed whether heightened awareness and rapid access to services impacted on the stage of presentation of colorectal cancer in our patient cohort over a 13-year period. Method: Data was extracted from a prospectively maintained database gathering information on all colorectal cancers at a District General Hospital. Five 12-month periods (2001, 2004, 2007, 2010 and 2013) were analysed specifically for the histopathological stage (American Joint Committee on Cancer), or the stage as assessed by imaging if inoperable or unresected. Data were analysed and presented graphically. Results: The number of 2-week wait referrals increased from 275 in 2001 to 1291 in 2013 whilst the number of cancers diagnosed increased from 161 in 2001 to 249 in 2013. The trend over a 13-year period is towards an increase in the number of stage I and II cancers (38.9% in 2001 to 43% in 2013) and a decrease in the numbers of stage III and IV cancers (61.1% in 2001 to 49% in 2013) diagnosed. Conclusion: The number of 2-week wait referrals has increased almost 5-fold over a 13-year period whilst the number of cancers diagnosed has only risen 1.5-fold. However, the number of cancers diagnosed has plateaued out in more recent years, despite the continuing rise in 2-week wait referrals. This perhaps reflects that the prevalence of colorectal cancer is not increasing in the general population. It also suggests that the 2-week wait referral system includes an increasing cohort of patients who may not need urgent investigation, with the consequential workload and financial implications. Similarly, the percentage of patients presenting with a stage III or IV cancer has not decreased further since 2007, when it was at a low of 44% of all colorectal cancers diagnosed. Whilst these results overall support the fast track referral process and campaigns to heighten awareness of colorectal cancer amongst the public and primary care physicians, they suggest that the effect of such measures in Gloucestershire is perhaps now maximised. Disclosure of interest: None Declared.